Ultrasonic Fingerprinting of Structural Materials: Spent Nuclear Fuel Containers Case-Study; Physics Procedia; Vol. 70 : International Congress on Ultrasonics (ICU) - Sednev D. A. Dmitry Andreevich; Lider A. M. Andrey Markovich; Demyanuk D. G. Dmitry Georgievich; Kroening H. M. V. A. Hans Michael Wilhelm Adolf; Salchak Ya. A. Yana Alekseevna (2015, 2015)
Title screen